Effects of Ambient Tropospheric Ozone on Mr-219 Rice in the Muda Irrigation Scheme Area - Ismail, Marzuki (2005)
Rice, the most important crop in Malaysia contributes about one-third of daily calorie intake among Malaysians, and it is the primary source of carbohydrates. As in many other developing countries in Asia, food security has been an integral national policy objective in Malaysia's development pursuits since the 1950s. The focus of the self-sufficiency programme has been on rice, as it is the staple food for the vast majority of the population. Domestic consumption of rice is projected to increase with increase in population; whereby the increase in production has to come from higher productivity in the existing granary areas since there is no plan to increase the area under paddy cultivation. It has long been recognized that pollutant gases cause significant impacts on crops and forests in both developed and developing countries. Tropospheric ozone (03) is recognised as the pollutant most likely to cause widespread crop damage. For this pollutant an AOT40 (accumulative O3 concentration above a threshold of 40 ppb) value causing 5% yield loss for all agricultural crops has been established as 3000 ppb.h, which is applicable during daylight hours over a growing season (UN-ECE, 1996). Comparatively, very few studies of tropospheric ozone impact on vegetation have been conducted in developing countries; majority of which; located along the equatorial belt. This is a serious omission because of the greater importance of this issue in developing countries due to increasing demand for higher crop production in the face of growing populations, rapid deterioration of ambient air quality associated with industrialisation and urbanisation as well as land constrains. Moreover, Malaysia, which is located at the equatorial region, may be at an even greater risk because the climate that is characterised by high temperature and high levels of solar radiation, promote the formation of photochemical pollutants such as 03. For the above purpose, there is a pressing need to determine the actual air pollution impacts on vegetation especially rice plant, which is the main staple food of Malaysia. Forecasting crop yield well before harvest is crucial to enable planners and decision makers to predict how much to import in case of shortfall or optionally, to export in case of surplus. It also enables governments to put in place strategic contingency plans for redistribution of food during times of famine. Therefore, monitoring of crop development and of crop growth, and early yield prediction is very crucial. In order to have a complete estimate of air pollution damage i.e., O3 to paddy plantation area, a dose-response, or yield-loss function have to be developed. In this study, data was gathered from tests in open-top chambers (OTCs), whereby four OTCs were fabricated; two of which were exposed to ambient air pollution (NF) of which ozone is the major perpetrator whilst the remaining were provided with clean air i.e. charcoal filtered air treatment (F). The response of a popular local rice cultivar, MR-219 to current ambient air pollution of which O3 is the overwhelming dominant pollutant was investigated for five successive seasons in Muda Irrigation Scheme Area (MADA); the largest and imperative rice growing area in Malaysia. This method has been widely employed to assess crop yield responses to ozone. The results of the study clearly indicate that at ozone concentrations even lower than the Malaysian air quality guidelines (60 ppb 8 hr mean) level, there exist a significant impact on the growth and yield of the popular rice cultivar MR-219. Even though weeds, diseases, and insect pests were absent, water and nutrients were in abundance, no adverse soil conditions, and that no extreme weather event such as typhoons occurs; the physiological, growth and development performances of rice plants exposed to ambient ozone were found to be significantly (P< 0.05) reduced by AOT40 compared to control rice plants in filtered chamber. This study discovered that the root was the most significantly affected component of MR-219 rice plant. Meanwhile, reproductive stage is the most vulnerable period of growth to ozone impact followed by grain filling and vegetative stages, respectively. For plant growth and development study, yield is the most critical parameter. Statistically, a square root-Y equation epitomize the best fitting compared to other curvilinear models in describing yield reduction of rice plant due to ambient O3 stress (DWFG); represented by the following equation: DWF,= [9.636 - (0.0000303 * AOT~O)].' This study finding is undeniable imperative and it bestows the first algorithmic yield-loss model of crop to ozone in this country, ever.